(untitled) (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2024)
This article aimed to analyze two types of addresses used in social groups for communication: formal and informal. The necessity to comply with official norms, the system of rights and duties and the norms accepted in social groups, and the existence of asymmetrical social relations all influence the type of formal appeal.